Maximum lift/drag ratio improvement of TUAVs via small aerodynamic modifications - Oktay, Tugrul; Uzun, Metin; Kanat, Ozturk Ozdemir (Emerald, 2018)
Purpose The purpose of this study is to increase maximum lift/drag ratio (Emax) of tactical unmanned aerial vehicles (TUAVs) via applying novel small aerodynamic modifications. Design methodology/approach A TUAV is manufactured in Erciyes University, Faculty of Aeronautics and Astronautics, Model Aircraft Laboratory. It has both passive and active morphing capabilities. Its nosecone and tailcone shapes are redesigned to improve Emax. Moreover, active flow control is also built on its wing for improving Emax. Findings Using these novel small aerodynamic modifications, considerable improvement on Emax is obtained. Research limitations/implications Permission of Directorate General of Civil Aviation in Turkey is required for testing TUAVs in real-time applications. Practical implications Small aerodynamic modifications such as nosecone-tailcone shape modifications and building active flow control on wing are very beneficial for improving Emax of TUAVs. Social implications Small aerodynamic modifications satisfy confidence, high performance and easy utility demands of TUAV users. Originality/value The study will enable the creation of novel approaches to improve Emax value and therefore aerodynamic performance of TUAVs.